1977
DOI: 10.1590/s0373-55241977000100005
|View full text |Cite
|
Sign up to set email alerts
|

Estudo das variações da relação peso total/comprimento total em função do ciclo reprodutivo e comportamento, de Sardinella brasiliensis (Steindachner, 1879) da costa do Brasil entre 23ºS e 28ºS

Abstract: SYNOPSISThis paper analyses some aspects on the length/weight relationship of Sardinella brasiliensis and its variations as a function of their reproductive cycle and displacements along the Brazilian coast between 23 0 S and 28°S. The area surveyed was divided into five subareas, each one covering one degree of latitude. The relationship and its variations between shoals were studied for each sub-area at different seasons and for the sub-are as at the same season. The absence of a variation pattern for the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
18

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 26 publications
(25 reference statements)
2
12
0
18
Order By: Relevance
“…Our results also show that there is an increase in individual weight resulting from gonad maturation (Braga, 1997), also documented for Sardinella brasiliensis by several authors (Vazzoler & RossiWongtschowski, 1976;Rossi-Wongtschowski, 1977;Isaac-Nahum et al, 1983Matsuura et al, 1992, Matsuura, 1998. The coefficient "a" can be identified as the allometric condition factor (Braga, TABLE 1: Sardinella brasiliensis: regression analyses ("a" and "b" regression coefficients of allometric model, r² = coefficient of determination) and relative growth analysis ("t" = t-test statistic, P = probability value of t-test, n = number of observations) by year and season (Su = Summer, Au = Autumn, Wi = Winter, Sp = Spring).…”
Section: Discussionsupporting
confidence: 88%
“…Our results also show that there is an increase in individual weight resulting from gonad maturation (Braga, 1997), also documented for Sardinella brasiliensis by several authors (Vazzoler & RossiWongtschowski, 1976;Rossi-Wongtschowski, 1977;Isaac-Nahum et al, 1983Matsuura et al, 1992, Matsuura, 1998. The coefficient "a" can be identified as the allometric condition factor (Braga, TABLE 1: Sardinella brasiliensis: regression analyses ("a" and "b" regression coefficients of allometric model, r² = coefficient of determination) and relative growth analysis ("t" = t-test statistic, P = probability value of t-test, n = number of observations) by year and season (Su = Summer, Au = Autumn, Wi = Winter, Sp = Spring).…”
Section: Discussionsupporting
confidence: 88%
“…This indicates an accumulation of reserves to accomplish reproduction, and by decreasing drastically during that period, caused by the expenditure of energy in such activity. Similar behavior was observed by Le Cren (1951), Rossi-Wongtschowski (1977), Isaac-Nahum & Vazzoler (1983); Barbieri (1992Barbieri ( , 1995 and Silva et al (2005;2007) in other fish species. The analysis of gonadal maturation confirm the above findings, indicating that the reproductive period of the species begins in September and extends to the end of December, with a peak in November.…”
Section: Discussionsupporting
confidence: 84%
“…The present study corroborates those results; however, statistical differences were not observed between the sexes regarding this coefficient. According to Rossi-Wongtschowski (1977), the length/weight relationship in fish may or may not show sexual dimorphism.…”
Section: Discussionmentioning
confidence: 99%
“…pescadores; as regiões II e IV constituem respectivamente dois locais de desova (Rossi-Wongtschowski, 1977); e a região III abrange ambientes costeirós abrigados: com condições ambientais distintas das de mar aberto.…”
Section: Methodsunclassified
“…tores sugeriram a existência de grupos distintos de S. brasiliensis ao longo da costa, entre Cabo Frio e Florianópolis (Besnard, 1950;Richardson et aI., 1959;Vazzoler & Ngan, 1976;Rossi-Wongtschowski, 1977). Tal heterogeneidade deve ocorrer tendo em vista as variações das condições oceanográficas e geográficas existentes na área.…”
unclassified